2019
DOI: 10.1242/jcs.229013
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the cellular mechanical microenvironment – from bulk mechanics to the nanoscale

Abstract: The field of mechanobiology studies how mechanical properties of the extracellular matrix (ECM), such as stiffness, and other mechanical stimuli regulate cell behaviour. Recent advancements in the field and the development of novel biomaterials and nanofabrication techniques have enabled researchers to recapitulate the mechanical properties of the microenvironment with an increasing degree of complexity on more biologically relevant dimensions and time scales. In this Review, we discuss different strategies to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 133 publications
1
33
0
Order By: Relevance
“…The ability to polarize in response to mechanical stimuli is fundamental for directed cell migration such as durotaxis or haptotaxis (King et al, 2016;Lachowski et al, 2017) and depends on differential, asymmetric activation of Rho GTPases such as RhoA and Rac1, which in turn orchestrate actin dynamics at the leading edge (Machacek et al, 2009;Cortes et al, 2019a). Accordingly, we found that actin polymerization and the RhoA/mDia system, which are regulated by GPER, are required for cell polarization and mechanosensing, in agreement with previous work that demonstrates that stiffness and haptotactic sensing by lamellipodia relies on RhoA-mediated actin protrusion, branching, and focal adhesion turnover (Puleo et al, 2019) independently from the ROCK/myosin-2 axis (King et al, 2016;Oakes et al, 2018;Matellan and Del Río Hernández, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The ability to polarize in response to mechanical stimuli is fundamental for directed cell migration such as durotaxis or haptotaxis (King et al, 2016;Lachowski et al, 2017) and depends on differential, asymmetric activation of Rho GTPases such as RhoA and Rac1, which in turn orchestrate actin dynamics at the leading edge (Machacek et al, 2009;Cortes et al, 2019a). Accordingly, we found that actin polymerization and the RhoA/mDia system, which are regulated by GPER, are required for cell polarization and mechanosensing, in agreement with previous work that demonstrates that stiffness and haptotactic sensing by lamellipodia relies on RhoA-mediated actin protrusion, branching, and focal adhesion turnover (Puleo et al, 2019) independently from the ROCK/myosin-2 axis (King et al, 2016;Oakes et al, 2018;Matellan and Del Río Hernández, 2019).…”
Section: Discussionsupporting
confidence: 91%
“…The cellular morphology and the direction of cell migration depends on properties such as the density and stiffness of the surrounding ECM components ( Yeung et al, 2005 ; Wehner et al, 2013 ; Charrier et al, 2018 ; Matellan and del Rıó Hernández, 2019 ). In fins, mesenchymal cells are mostly shaped rounded at the base region and are elongated at the fin tip region.…”
Section: Discussionmentioning
confidence: 99%
“…At this scale, mechanical properties, such as tissue stiffness, can vary widely depending on multiple factors including local cellular tension, ECM composition, and flow conditions, leading to inaccuracies in the description of the mechanical environment. [ 11,135,137,138 ] The challenges in implementing existing measurement techniques to characterize engineered, vascularized microstissues have hindered the mechanistic understanding of vascular development and vascular disease progression in complex 3D environments. However, novel approaches to measure cell‐generated forces and material properties have emerged that can begin to fill this gap.…”
Section: Measuring Cell and Tissue Mechanical Properties For Mechanotmentioning
confidence: 99%